RETRACTED: Basic issues in the development of grain production in the Republic of Armenia in the context of food security - Ghukasyan Abraham; Aleqsanyan Vardan; Matinyan Alvard; Merujan Galstyan; Matevosyan Lusine (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001